Assessment of Slope Instability Caused by Weathering Process in Pergau-Batu Melintang, Kelantan - Wahab W.A.; Omar R.C.; Jaapar A.R.; Taher T.M.; Roslan R.; Baharuddin I.N.Z.; Solemon B.; Khalid N.H.N.; Isa A.A.M.; Zarime N.A. (Springer Science and Business Media Deutschland GmbH, 2024)
This paper aims to assess the subsurface integrity and stability of the slope in the Pergau-Batu Melintang electrical energy production area, located on a highland and near the slope edge, which may pose a risk. Two geophysical survey techniques were used to evaluate the slope's stability: electrical resistivity and seismic survey through in situ testing. The electrical resistivity test has the advantage of producing both subsurface resistivity and the ground's resistivity index. Meanwhile, the seismic survey aimed to identify any subsurface homogeneity. This study assessed the slope stability due to rock weathering by combining in situ testing, geophysical survey, laboratory testing, rock quality designation (RQD%), standard penetration test (SPT) N values, and macroscopic and microscopic rock identification. Slope-W software was used to simulate and determine the slope's Factor of Safety (FOS). The FOS results indicate that the method utilised in this study offers a promising discovery and a correlation between the impact of weathering processes and slope instability. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.